Isolation and characterization of fungal pathogen isolated from infected seeds of oil palm / Nur Nadhirah Hannan Zamzuri - Zamzuri, Nur Nadhirah Hannan (2018)
Oil palm is known as one of major contributions to national’s economy. Diseases that caused by fungal pathogen are the major cause of yield and quality declining to oil palm plantations. Brown germ and seed rot were the most diseases detected during seed stage in oil palm plantations. The present study was conducted to isolate and morphologically characterize the fungal pathogen from infected seeds of oil palm and to prove that the fungal pathogen consistently a causative agent of seed disease. The infected seed was observed through its symptoms such as brown color of both plumule and radicle with stubby radicle. The isolated fungal from infected seed was designated as seed oil palm 1 (SOP1). The microscopic observations of SOP1 were hyaline and smooth-walled conidiophores, globose shape of conidia, biseriate phialides, radiate conidial heads and septate and hyaline of hyphae. The identification of SOP1 was proposed belonged to the genera of Aspergillus species. Healthy seed that has been infected with SOP1 showed similar symptoms as infected seed. The microscopic observations of re-isolated SOP1 from the re-infected healthy seed displayed similar morphology as SOP1. Hence, morphological, macroscopic and microscopic method was important for identification of Aspergillus species that caused several diseases to oil palm seeds. From the macroscopic and microscopic observations, it can be concluded that Aspergillus species proved to be a causal agent of several diseases in oil palm seeds.